Interventions on the Perceptions of Student Teachers’ Use of WhatsApp in Teaching Methods of English as a Second Language Classroom in Namibia - Mbukusa, Nchindo Richardson (An Overview of Literature, Language and Education Research Vol. 8, 2024)
The mobile phone has become the preferred means of communication, especially among young people, and there are many teachers who are committed to introducing it as a resource in their classrooms. Mobile devices and their features have been in the glare of publicity for educational purposes WhatsApp, in this case, increases learning opportunities for students to work smarter and more effectively. This research investigated students’ perceptions towards using the WhatsApp application as a learning tool for Teaching Methods of English as a Second Language on a Bachelor’s Degree in Education. The study employed a mixed methodology where the first part of it was done in 2018 and followed in 2024. To achieve this, about 99 students in the same cohort completed the self-administered questionnaires. Another six students were followed and interviewed after they had been in the field for about two years. The study revealed, among many, that the use of WhatsApp can impact negatively the performance of students who do not own smartphones while students with smartphones do well. The platform shows a variance in balancing online activities (WhatsApp) and academic preparation and distracts students from completing their assignments and adhering to their private studies timetable. However, students enjoy using WhatsApp as a tool for learning and call for institutions to offer internet amenities as a top urgency in contemporary instruction. Teachers need to create learning opportunities for students on the platform that encourage all to join and learn. Such opportunities are good for peer-to-peer learning opportunities, whether synchronous or asynchronous.